Impact on Health-Related Quality of Life and Costs of Managing Chronic Neuropathic Pain in Academic Pain Centres: Results from a One-Year Prospective Observational Canadian Study - J-E Tarride; DE Moulin; M Lynch; AJ Clark; L. Stitt; A Gordon; PK Morley-Forster; H Nathan; C Smyth; C Toth; MA Ware (Pain Research and Management)
BACKGROUND: The management of chronic pain, including neuropathic pain (NeP), is a major public health issue. However, there is a paucity of data evaluating pain management strategies in real-life settings.